TERRITORIAL FEATURES OF THE DEVELOPMENT OF THE SERVICE SECTOR IN THE CONDITIONS OF INNOVATIVE DEVELOPMENT OF THE ECONOMY - Primova Sh.J.; Ravshanova D.Sh. (Scholar Express Journal, 2023)
The article covers such concepts as sales service, sales service quality, and sales culture. It analyzed the indicators of the quality of sales service provided to customers at the "Korzinka.uz" supermarket in cities and made recommendations for their improvement.
Keywords: retail trade; trade culture; trade service quality